Dub3 controls DNA damage signalling by direct deubiquitination of H2AX. Issue 5 (18th March 2014) - Delgado-Díaz, M. Rocío; Martín, Yusé; Berg, Anna; Freire, Raimundo; Smits, Veronique A.J.
Abstract : A crucial event in the DNA damage response is the phosphorylation and subsequent ubiquitination of H2AX, required for the recruitment of proteins involved in DNA repair. Here we identify a novel regulator of this process, the ubiquitin hydrolase Dub3. Overexpression of wild type, but not catalytic inactive, Dub3 decreases the DNA damage‐induced mono‐ubiquitination of H2A(X) whereas downregulation of Dub3 has the opposite effect. Dub3 overexpression abrogates focus formation of 53BP1 and BRCA1 in response to genotoxic stress. However, focus formation of MDC1 and γH2AX, earlier events in this response, are unaffected by Dub3 overexpression. We show that Dub3 counteracts H2AX E3 ligases RNF8 and RNF168. Moreover, Dub3 and H2AX interact and Dub3 deubiquitinates H2AX in vitro. Importantly, overexpression of Dub3 delays H2AX dephosphorylation and recovery of MDC1 focus formation at later time points after DNA damage, whereas H2AX dephosphorylation at later time points is faster after Dub3 depletion. Altogether these results show that Dub3 regulates a correct DNA damage response by controlling H2AX ubiquitination. Highlights: We identified a novel ubiquitin hydrolase of H2A(X). Overexpression of Dub3 decreases DNA damage‐induced H2A(X) monoubiquitination. Dub3 overexpression abrogates 53BP1/BRCA1 focus formation, but not γH2AX/MDC1. Dub3 and H2AX interact and Dub3 deubiquitinates H2AX in vitro. Dub3 expression impairs DNA repair as measured by delayed H2AX dephosphorylation.